(untitled) (Innovative professional education, 2024)
The development of digital competences of teachers of vocational education and training in the context of training skilled workers for the engineering industry is considered. The importance of integrating digital technologies into the educational process to ensure effective training of vocational education students to the requirements of modern engineering production is emphasized. It is noted that the continuous professional development of teachers and the introduction of the latest technologies are key to successful learning.